2005
DOI: 10.1002/cncr.21043
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional conformal radiotherapy for portal vein thrombosis of hepatocellular carcinoma

Abstract: BACKGROUND Portal vein thrombosis (PVT) is a common complication in patients with advanced‐stage hepatocellular carcinoma (HCC). The authors evaluated the impact of radiotherapy (RT) for PVT of HCC and analyzed the dose‐response relation between RT and PVT. METHODS Between March 1995 and December 2003, 59 patients diagnosed as HCC with PVT were included. The inclusion criteria were unresectable tumor with thrombosis in the main or first branch of the portal vein, liver function of Child–Pugh Class A or B, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
151
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(163 citation statements)
references
References 27 publications
7
151
3
Order By: Relevance
“…Although TACE appears to have potential for providing a survival benefit for HCC patients with PVTT, with a median PFS of 3.6-5.1 months (54,55), the deteriorating liver function caused by TACE limits its application (56,57). By contrast, hepatic resection may produce superior survival benefits for HCC patients with PVTT, with a 1-year overall survival rate of 34.4-42.0% (58)(59)(60)(61), and radiotherapy may have superior local effects in these patients (62,63). The prognosis of HCC patients with PVTT is dismal.…”
Section: Univariate Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Although TACE appears to have potential for providing a survival benefit for HCC patients with PVTT, with a median PFS of 3.6-5.1 months (54,55), the deteriorating liver function caused by TACE limits its application (56,57). By contrast, hepatic resection may produce superior survival benefits for HCC patients with PVTT, with a 1-year overall survival rate of 34.4-42.0% (58)(59)(60)(61), and radiotherapy may have superior local effects in these patients (62,63). The prognosis of HCC patients with PVTT is dismal.…”
Section: Univariate Analysismentioning
confidence: 99%
“…Shi et al demonstrated that liver resection with portal thrombectomy for HCC cases with PVTT, compared with resection without portal thrombectomy, is justified in selected patients with PVTT located in the segmental or sectoral branches of the portal vein (61). Zhang et al suggested that percutaneous transhepatic portal vein stenting (PTPVS)-TACE combined with three-dimensional conformal radiotherapy (3-DCRT), compared with PTPVS-TACE without 3-DCRT, is possibly an effective treatment modality for HCC with PVTT (63).Kim et al noticed that radiotherapy induced a 45.8% objective response rate for PVTT in patients with HCC, and considered that radiotherapy may be a treatment option for PVTT in patients with HCC (62).…”
Section: Univariate Analysismentioning
confidence: 99%
“…11,13,25 Meanwhile, the combination of TACE and local radiotherapy has been applied continuously to primary HCC which cannot be resected, and its positive outcomes of enhancing the survival rate have been reported. 12,30 In particular, antitumor agents, which were used during TACE to tumor cells on the tumor margin, work as radiosensitizers not only to increase the effect of radiotherapy but also to make TACE available by improving portal vein thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…8 Providing a high-dose irradiation as a local irradiation, not the whole liver irradiation, has been identified, which has been continuously reported that the combination therapy of radiotherapy and chemotherapy or TACE for HCC works favorably. [9][10][11] What is more, in case of the patients who are not under other treatments or associating with portal vein thrombosis, [12][13][14][15] radiotherapy was safe and effective to raise the survival rate. 16 The radiotherapy had the effect of relieving cancer pain, improving symptoms through the decrease of lesions, lengthening the survival time in the circumstances with the biliary obstruction of a tumor associated with jaundice, 17,18 and extending the survival time in patients with abdominal lymph node metastasis.…”
Section: Introductionmentioning
confidence: 98%
“…The rational for this approach is that RT targets cancer cells at the tumors periphery that may remain viable through blood supply from collateral circulation or recanalization of the embolized artery (51). The third approach, tumor shrinkage after TACE allows the use of smaller irradiation fields, which permits higher tumor doses and improves normal liver tolerance (52). Furthermore, the TACE anticancer drugs retained in the tumor may have a radiosensitizing effect (53,54).…”
Section: Sbrt Combination With Tace For Inoperable Hccmentioning
confidence: 99%